Thin Film Deposition and Characterization Techniques - Geremew, Temesgen (Journal of 3D Printing and Applications, 2022)
Thin films are everywhere in the modern world, with many of the technologies we depend upon in daily life being, in turn, dependent upon thin film technology. Chemical bath deposition includes principles of chemical bath deposition (CBD) and concept of solubility product, nucleation and film growth, thin film deposition mechanism in chemical bath deposition. The non-metallic ion source (anions) and metal ion source (cations) then react to form the compound. The nucleation process plays an important role in determining the crystallinity and microstructure of the resultant film. From the discussion of deposition techniques which are physical and chemical deposition methods. Physical deposition techniques contains sputtering deposition, electron beam evaporation and physical vapour deposition (PVD) process have been known for over 100 years and also fabrication films on the substrate, as well as the increasement of the pressure in the chamber due to operation of the sources indicates directly that gases or vapors are desorbed. Chemical deposition process is economically effective and has been industrially exploited to large scale. It can be summarized that thin film characterization techniques include X-ray diffraction (XRD), UV-Vis spectrophotometer, scanning electron microscopy, energy dispersive x-ray diffraction, transmission electron microscopy (TEM). X-rays diffraction (XRD) is a rapid and a powerful technique used to study the phase of a crystalline material, information on unit cell lattice parameters, crystal structure, crystal orientation and crystalline size.
Keywords: Physical Methods; Chemical Methods; Thin Films; Chemical Bath Deposition; Characterization of Thin Films; Physical Vapour Deposition